Pengembangan Bahan Ajar Digital Flipbook Dalam Meningkatkan Kompetensi Guru TK di TK Citra Indonesia - Satria, Andy; Ramadhani, Fanny; Salamah, Salamah (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Improving the quality of learning at the basic education level, especially in Kindergarten (TK), is an urgent need in facing the demands of developments in information technology. This service aims to develop and evaluate digital teaching materials in the form of Flipbooks as an innovative means of improving the competency of kindergarten teachers at Citra Indonesia Kindergarten. The development method used is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, which involves needs analysis, design, development, implementation and evaluation of digital teaching materials. The Flipbook digital teaching materials developed focus on increasing kindergarten teachers' understanding and skills in managing interesting and interactive learning. The materials presented are designed to fulfill the kindergarten curriculum and integrate technology as a learning medium that can motivate pre-school children. The implementation of Flipbook in learning activities at Citra Indonesia Kindergarten is carried out through intensive training and mentoring to ensure teachers' mastery of technology. The evaluation was carried out through observation, interviews and questionnaires to measure the effectiveness of using Flipbook digital teaching materials in improving the competence of kindergarten teachers. The evaluation results show a significant increase in understanding of interactive learning concepts and mastery of technology by kindergarten teachers. Therefore, the development of Flipbook digital teaching materials can be an effective alternative in improving the quality of learning at Citra Indonesia Kindergarten, as well as stimulating teacher creativity and motivation in teaching.